Security and Defence Issues, New Zealand, 1985 (ADA Dataverse, 2018)
Topics in this survey include: importance of ANZUS; US or New Zealand benefits more from ANZUS; ANZUS and risk of attack of New Zealand; ANZUS and peace in East Asia and Pacific region; ANZUS prevents nuclear war and increases Australia and other Western countries security; cost of New Zealand defence if not in ANZUS; increased New Zealand spending on its own defence; New Zealand access under ANZUS to US technology, training and military hardware; ability of New Zealand to defend itself; trust in US to come to New Zealand's defence; US would come to New Zealand's defence if not an ally; New Zealand and ANZUS responsibilities; New Zealand security and US naval forces in Western Pacific and Indian Oceans; threat posed to New Zealand security by USSR naval forces now and in 5 years; visits by US warships with nuclear powered engines; visits by US warships that might be carrying nuclear weapons; ANZUS responsibilities and visits by US warships; arguments for and against visits by US warships; damage to ANZUS by New Zealand ban to US nuclear warships; damage to New Zealand and US relationship. Standard variables include self-placement on left-right spectrum, household size, age, marital status, schooling, occupation of respondent or of main income earner, household income, sex, area. This study is the last of four (SSDA No's 521 to 524) commissioned by the United States Information Service between 1982 and 1985 on New Zealanders' attitudes to defence issues. Similar studies were carried out in Australia at the same time (SSDA No's 525 to 532) which contain some parallel questions.